Fifty years of coronary artery bypass grafting - Melly, Ludovic; Torregrossa, Gianluca; Lee, Timothy; Jansens, Jean-Luc; Puskas, John D. (Journal of Thoracic Disease; Vol 10, No 3 (March 31, 2018): Journal of Thoracic Disease, 2018)
Coronary artery bypass grafting (CABG) remains the most common cardiac surgery performed today worldwide. The history of this procedure can be traced back for more than 100 years, and its development has been touched by several pioneers in the field of cardiac surgery, who have contributed with both their successes and failures. With ever increasing follow up and number of patients treated, thinking regarding optimal CABG technique evolves continually. This article reviews the history of CABG from its early experimental work to recent technological advances.